Does Tourism Reduce Poverty in Sub-Saharan African Countries? (2020)
To achieve the Sustainable Development Goals (SDGs), precisely the one of eradicating extreme poverty at the end of 2030, it is important to understand factors that can reduce poverty. This article examines the effects of tourism development on poverty in Sub-Saharan African countries. Because of the possibility of an endogeneity problem arising from a reverse causation that might exist between poverty and the explanatory variables, the system Generalized Method of Moments (system GMM) estimation technique was deployed. The findings showed that tourism development contributes to poverty reduction in Sub-Saharan African (SSA) countries. In other words, the results obtained provided ample support for the workability of a pro-poor tourism policy agenda. As a result, policies that are targeted at increasing the attractiveness and awareness of the existing SSA tourism sites in order to increase international tourism receipts and arrivals should be promoted since such interventions have considerable poverty reduction potential.